Bringing Morgan’s metaphors in organization contexts: An essay review - Iman Tohidian (Taylor & Francis Group, 2019)
Recently, the issue of metaphors in organizational studies has fascinated researchers’ attention and interests, leading to a substantial body of research generating theoretical understandings, philosophical concepts, insightful meanings, and experiential interpretations. In this review paper, the researchers critically approached reading and reviewing the studies which have been undertaken so far in order to achieve an orientation in metaphorical research on organizations. So, at first, Gareth Morgan’s Images of Organization in terms of different metaphors were discussed and elaborated. Then, the review of a number of papers illustrated that a majority of research works on this issue focused on the theoretical and conceptual aspects of organizational metaphors without taking their practicality in real contexts into account. Based on this review paper, it is suggested that in order to enrich this area with innovative ideas, understandings, and insights, there is a need for further research which targets the practical use of metaphors in organizations.